The Influence of Financial Compensation on Employee Performance at Village Offices in East Pasimasunggu District, Selayar Islands Regency - Nur Annisa; Dg. Maklassa; Sitti Mahrumi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study aims to analyze the effect of financial compensation on employee performance at village offices throughout Pasimasunggu Timur District, Selayar Islands Regency. The background of this research is based on the importance of financial compensation as one of the motivational factors that can influence employee productivity and work effectiveness in supporting the achievement of organizational goals. This research employed a quantitative approach with a survey method by distributing questionnaires to the entire population of 40 employees, using a saturated sampling technique. The data were analyzed using validity tests, reliability tests, classical assumption tests, and simple linear regression analysis with the help of SPSS v16.0 for Windows. The results of the study show that financial compensation has a positive and significant effect on employee performance, with a coefficient of determination of 47.5%. This means that 47.5% of the variation in employee performance can be explained by financial compensation, while the remaining 52.5% is influenced by other factors not examined in this study. The implications of these findings emphasize that improving financial compensation policies that are fair, adequate, and aligned with employees’ needs will encourage job satisfaction and enhance work motivation, which directly contributes to better performance. This study provides practical contributions for village governments in designing more effective compensation systems, as well as academic contributions in strengthening the study of human resource management, particularly in the village government sector.